Primary Leiomyosarcoma of Breast: A case report from Nepal - K C, Manisha; Amatya, Kapendra Sekhar; K C, Alissa; Bhattarai, Pratik; Shah, Sreya; Rana, Nabin (Nepalese Journal of Cancer, 2023)
Leiomyosarcoma is an uncommon form of breast cancer, accounting for 5-10% of all breast sarcomas with only 704 instances recorded to date. Waterwarth described the first instance of primary leiomyosarcoma breast (PLB) in 1968. This is the first case of PLB documented in Nepal, that we’re aware of. Leiomyosarcoma is a malignant non-epithelial smooth muscle tumor that can occur anywhere in the body. We discuss the case of a 41-year-old female who presented with a breast lump that was subsequently confirmed as Primary leiomyosarcoma and was treated with wide local excision with margins. We've been watching her progress for a year.